2007
DOI: 10.1111/j.1365-2559.2007.02755.x
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of fascin in oral and oropharyngeal squamous cell carcinomas has prognostic significance – a tissue microarray study of 129 cases

Abstract: Expression of fascin protein may play an important role in progression of OSCC. Overexpression of fascin contributes to a more aggressive clinical course and suggests the potential of fascin as a new molecular target for therapeutic intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
5
33
0
Order By: Relevance
“…More than 95% of invasive pancreatic tumors and 89% of non-small cell lung carcinomas express high levels of fascin (1) In another study, fascin expression levels were correlated with histological grade in glial astrocytic tumors and fascin overexpression may play an important role in the prognosis of glioblastoma multiformes (15) Higher immunostaining fascin scores were strongly associated with advanced grades advanced T stages of pancreatobiliary adenocarcinomas (16). In oral and oropharyngeal squamous cell carcinoma, fascin protein was overexpressed in carcinoma cells compared with their non-neoplastic epithelial counterparts (17,19). In addition, expression of fascin in lung, gastric, esophageal carcinoma has correlated with more advanced stage, poor prognosis and or decreased survival time (1,8,30).…”
Section: Dıscussıonmentioning
confidence: 97%
See 1 more Smart Citation
“…More than 95% of invasive pancreatic tumors and 89% of non-small cell lung carcinomas express high levels of fascin (1) In another study, fascin expression levels were correlated with histological grade in glial astrocytic tumors and fascin overexpression may play an important role in the prognosis of glioblastoma multiformes (15) Higher immunostaining fascin scores were strongly associated with advanced grades advanced T stages of pancreatobiliary adenocarcinomas (16). In oral and oropharyngeal squamous cell carcinoma, fascin protein was overexpressed in carcinoma cells compared with their non-neoplastic epithelial counterparts (17,19). In addition, expression of fascin in lung, gastric, esophageal carcinoma has correlated with more advanced stage, poor prognosis and or decreased survival time (1,8,30).…”
Section: Dıscussıonmentioning
confidence: 97%
“…In the literature the absence or low expression of fascin in normal epithelia is dramatically altered in many human carcinomas and overexpression may play an important role in the biologic behaviour of glial astrocytic tumor, oropharyngeal squamous cell carcinoma, colorectal cancer, bile duct carcinoma, renal cell carcinoma, pancreatic carcinoma, lung carcinoma (11,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Fascin expression is also increased in epstein-Barr virus-transformed B lymphocytes in the Reed-Steinberg cells of Hodgkin's lymphoma (27,28).…”
Section: öZmentioning
confidence: 99%
“…Other investigations have also reported the overexpression of fascin in various cancer tissues and cell lines, some of which indicated a positive association with poor prognosis and aggressiveness. [4,8,[27][28][29][30] Comparison of different SCC cell lines has shown that tumors with a higher degree of aggressiveness, demonstrate stronger fascin expression. [5,30] This could be explained by the cellmotility-promoting characteristics of fascin that leads to facilitation of cellular movement, required for invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…[3] In order to metastasize, malignant cells undergo a series of complex events, during which they achieve significant motile properties leading to increased migratory abilities and invasion of surrounding tissues and vasculature. [3][4][5] Cellular movement requires redistribution of cytoskeletal actin into parallel bundles to provide additional strength for cell protrusions in the form of filopodia or lamellipodia. [3,5,6] These projections are regulated by a number of proteins like fascin.…”
Section: Introductionmentioning
confidence: 99%
“…Fascin has emerged as an interesting potential biomarker due to its low or absent expression in the majority of normal adult epithelia; colonic (9), breast (10), ovarian (11), stomach (12), pancreas (13), oral cavity (14,15), oropharynx (15), nasopharynx (16) and larynx (17), yet fascin upregulation has been reported in all types of human carcinoma that has been studied to date (17,18). Consistently, primary carcinomas, with high levels of fascin, correlate with a clinically more aggressive disease and poor prognosis (19).…”
Section: Introductionmentioning
confidence: 99%